The octograph and the delight of understanding organizational artistry: How to enjoy social interaction and stimulate job performance? - Abdel Magid Al-Araki (Open Economics, 2019)
This paper proposes the Octograph, a cube-like model of leadership and organizational performance. Eight concepts, placed on eight corners of the cube, create eight triangular models and four processes of Decision-making, Communication, Production and Innovation. The eight concepts are nested together through one-arrowed dependency lines. Saying «Leadership» depends more on «employees» than vice versa, presupposes causal explanations of the how and why of the dependency.
Keywords: 330; Throughput; Associative thinking; Modelling; Oscillation